Win the second balls! The impact of strategic ball recovery on match performance in elite soccer - Sunjic, I.; Pavlinovic, V.; Skomrlj, J.; Morgans, R.; Modric, T. (International Journal of Performance Analysis in Sport, 2025)
This study aimed to determine the influence of winning second balls on technical performance separately by each pitch third. Data was obtained from all matches played in two recent FIFA World Cups held in 2018 and 2022. Employing linear mixed models, results revealed that winning second balls in the (i) first area of the pitch was positively associated with the total number of shots and shots inside the box, ball receives in the final third and in the box, total and forward passes, dribbles, and corners (Cohen`s d = 0.30-0.70); (ii) second third of the pitch was not associated with any of the technical performance variables; (iii) final area of the pitch was positively associated with ball receives in the final third and in the box, total and forward passes, and corners (Cohen`s = 0.39-0.59). These findings indicated that winning more second balls in the first and final third may enhance teams` key offensive technical performance. This study provided soccer practitioners with applicable solutions regarding zone occupation strategies during duels and emphasised the importance of using training scenarios that improve their ability to win second balls.